PENGARUH BIMBINGAN KELOMPOK BERBASIS RELIGIUS TERHADAP REGULASI DIRI SISWA PADA MASA PANDEMI COVID 19 - RAISUL ISLAMI (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2022)
This study aims to analyze the effect of religious-based group guidance on the religious beliefs of state junior high school students in Muaro Jambi Regency. This research uses quantitative methods with the type of survey research. According to Glock and Stark, the religious dimension consists of 5 dimensions, namely: religious belief (religious belief), worship practice (religious practice), religious appreciation (religious felling), religious knowledge (religious konowledge) and religious practice (religious effect). In this study only discuss the dimensions of religious belief (religious belief). Quantitative data was obtained by distributing a questionnaire containing a Likert scale assessment, using the google form application which was sent to class IX students of SMP Negeri Muaro Jambi Regency, Data Processing using SPSS 25. This was done due to the Covid-19 pandemic. The population in this study was 1332 students, consisting of 16 public junior high schools throughout Muaro Jambi Regency, Jambi Province. While the determination of the sample in this study using the Slovin formula with a significance level of 95% and an error rate of 5%. From the results of using the formula, the number of samples was 310 students. Sampling using simple random sampling technique, which is done randomly without considering the strata this is because the sample is homogeneous. From the results of the study, it was found that the average self-regulation variable (Y) was 73.10 with an achievement level of 83.22% categorized as good. While the variable of religious belief (X) with an average of 26.86 with an achievement level of 89.52% is categorized as good. ABSTRAK Penelitian ini bertujuan untuk menganalisis pengaruh bimbingan kelompok berbasis religius terhadap terhadap keyakinan beragama siswa SMP Negeri se- Kabupaten Muaro Jambi. Penelitian ini dengan metode kuantitatif dengan jenis penelitian survey. Menurut Glock dan Stark dimensi religius terdiri dari 5 dimensi, yaitu: keyakinan beragama (religius belief), praktek ibadah (religius practice), penghayatan agama (religius felling), pengetahuan keagamaan (religius konowledge) dan pengamalan agama (religius effect). Dalam penelitian ini hanya membahas dimensi keyakinan beragama (religius belief). Data kuantitatif diperoleh dengan menyebarkan kuesioner yang berisi penilaian skala Likert, dengan menggunakan aplikasi google form yang dikirim kepada siswa kelas IX SMP Negeri Kabupaten Muaro Jambi tahun 2022, Pengolahan Data menggunakan SPSS 25. Hal ini dilakukan karena Pandemi Covid-19. Populasi dalam penelitian ini sebanyak 1332 orang siswa, yang terdiri dari 16 SMP Negeri se-Kabupaten Muaro Jambi Provinsi Jambi. Sedangkan penentuan sampel dalam penelitian ini menggunakan rumus Slovin dengan tingkat signifikansi 95% dan tingkat error 5%. Dari hasil penggunaan rumus tersebut diperoleh jumlah sampel sebanyak 310 siswa. Pengambilan sampling menggunakan teknik simple random sampling, yang dilakukan secara acak tanpa mempertimbangkan strata hal ini disebabkan karena sampel bersifat homogen. Dari hasil penelitian ditemukan rata variable regulasi diri (Y) sebesar 73,10 dengan tingkat capaian 83,22% dikategorikan baik. Sedangkan variable keyakinan beragama (X) dengan rata-rata 26,86 dengan tingkat capaian 89,52% dikategorikan baik.